Six crows : a fable - Lionni, Leo, 1910- (New York : Knopf, 1988)
An owl helps a farmer and some crows reach a compromise over the rights to the wheat crop.
"A Borroi book"--Colophon.
Booklist
3.9
K-3
Keywords: Farm life -- Fiction; Crows -- Fiction; Farm life -- Fiction